[Portrait of Phillip Adams attending an address by Joan Kirner, Chair of the Centenary of Federation Advisory Committee at the National Press Club, Canberra, 10 August, 1994] - Long, Andrew Stawowczyk; National Library of Australia (1994)
Part of a collection of portraits taken during and address by Joan Kirner, Chair of the Centenary of Federation Advisory Committee, at the National Press Club, Canberra on 10 August, 1994. Also photogaphed in the audience were Phillip Adams and Rosemary Follett.
Title devised by cataloguer from information on negative packets.
Condition good.
Negative to be found in packet (B) of 3 packets (A, B & C).
Also available online
National Library of Australia Oral History section ORAL TRC 4452
Keywords: Adams, Phillip, -- 1939- -- Portraits; Broadcasters -- Australia -- Portraits; Authors, Australian -- Portraits; Broadcasters; Authors